COVID-19 vaccination intention among people who use drugs in France in 2021: results from the international community-based research program EPIC - C. Lacoux; V. Villes; L. Riegel; S. Coulmain; N. Lorente; S. Eddine Derras; D. Rojas Castro; P. Roux; R. M. Delabre; D. Michels (Harm Reduction Journal)
Abstract Background COVID-19 vaccination is crucial to reduce the incidence of severe forms of the disease in the population. However, people who use drugs (PWUD) face structural and individual barriers to vaccination, and little is known about vaccination intention and factors associated with that intention among PWUD. This study aimed to estimate vaccination intention in PWUD and associated factors in the early stage of vaccination campaigns. Methods We conducted cross-sectional study in France among PWUD, as part of the international EPIC program, a community-based research study coordinated by Coalition PLUS. It included 166 unvaccinated PWUD attending harm reduction centers. A questionnaire collected data on sociodemographic characteristics, COVID-19 related difficulties, and mental health, among other things. Multivariate logistic regression was used to identify factors associated with low vaccination intention. Results Only 19% of participants reported strong intention to get vaccinated against COVID-19. Factors independently associated with low vaccination intention were younger age (aOR = 0.90, 95%CI = 0.85–0.95), lower education level (aOR = 2.67, 95% CI = 0.95–7.55), and unstable housing (aOR = 6.44, 95% CI = 1.59–40.34). The most-cited reasons for low intention were mistrust in COVID-19 vaccines (66.1%), fear of side effects (48.7%), and non-belief in vaccinations in general (25.2%). Conclusions This study highlights the need for targeted COVID-19 information and interventions to increase vaccine uptake in PWUD, especially those living in precarity. Community-based interventions and targeted government assistance could play a crucial role in addressing vaccine hesitancy in this population, not only for COVID-19 but for future epidemics.